The Effect of Transformational Leadership on Organizational Citizenship Behavior E-Government Based - Farizah, Fitri; Muliawaty, Lia (ann4publisher@gmail.com, 2024)
The background of this research highlights the importance of Transformational Leadership for the application of information technology in local government in Indonesia, primarily through the implementation of the Electronic-Based Government System (SPBE) in Sumedang Regency with innovative efforts such as e-Office applications have marked a commitment in implementing technology to improve public services. However, the critical role of regional heads and organizational structures, especially the head of the General Section at the Sumedang Regional Secretariat, is still faced with significant challenges related to technology adoption, integration of modern applications, and human resource management that have not been in line with the digital era. Quantitative research methods were used to investigate the relationship between Transformational Leadership and Organizational Citizenship Behavior (OCB) with data analysis using SPSS. Data were obtained through surveys, interviews, questionnaires, and related documentation. The analysis showed a positive, albeit weak, relationship between Transformational Leadership and OCB. However, a low correlation (0.381) indicates a minimal relationship. A high p-value (0.26) indicates the statistical insignificance of this relationship. Regression confirms that changes in Transformational Leadership do not significantly affect OCB. A low R Square (0.112) indicates that Transformational Leadership explains only a tiny percentage of OCB behavior. Despite the positive relationship, Transformational Leadership is needed to drive more significant changes in the application of technology and improvement of public services in the local government of Sumedang.